Health risks of climate change in the 21 Pacific Island states and noted gaps in scientific evidence: A scoping review - Hyun Kim; Andrew Ryan; Alyson B. Harding; Adam F. Moskowitz; Alexander I. Passe; Erin C. Kawazu (Elsevier, 2022)
The Pacific Islands, a group of Small Island Developing States (SIDS), are thought to be particularly vulnerable to the consequences of climate change, highlighting the critical need for holistically assessing risks, especially those relevant to the health and wellbeing of local communities. This scoping review assesses the state of peer-reviewed literature on the health risks associated with climate change in the 21 Pacific Island states, analyzing quantitative and qualitative studies focusing explicitly on health outcomes, as well as studies focusing on health determinants or potential mediators along the climate-health pathway. The evidence in the Pacific is limited and largely geographically centered on a select few states, but highlights that climate change indicators are associated with a wide range of health outcomes, including but not limited to diarrhea, leptospirosis, typhoid fever, and mental distress. With respect to mediators, the review also reveals that infrastructural systems and policies are not sufficient to protect communities from potential health consequences in the states studied. By matching the review findings to the recommendations of the WHO Framework for Building Climate Resilient Health Systems, the paper highlights critical gaps in evidence regarding components of the framework such as climate-resilient technology, infrastructure, and climate-resilient financing. Although limited, the evidence reveals priority areas for climate adaptation. Further research that includes a focus on quantitative assessments of climate-related interventions will be critical to building resilience in one of the most at-risk regions of the world.